Effectiveness of Local Product Marketing Communication on Consumer Purchase Intention in Sorong Regency Southwest Papua - Luvnaya Nazhwa Arifai; Herviana Puspita Cahyati; Sopian; Fajar Kurniawan Lunggu; Rosita Nanda Wulandari; Frisca Tria Ramadhani; Andi Sismar; Anita Kusumawati (www.amertainstitute.com, 2025)
This study aims to analyze the effectiveness of local product marketing communication on consumer purchase intention. Effective marketing communication is believed to be able to build positive consumer perceptions of local products, which in turn influence purchasing decisions. A quantitative approach was used in this study with a survey method of 150 respondents who are active consumers of local products. The research instrument was a questionnaire compiled based on valid indicators from marketing communication theory and consumer behavior. The results showed that marketing communication has a significant direct influence on consumer purchase intention (p <0.05). This finding confirms the importance of communication strategies in increasing the competitiveness of local products in an increasingly competitive market. The practical implications of this study encourage local business actors to optimize digital communication channels.